Education as a Fundamental Element in Ensuring the National Security of the State - Vasilii A. Dadalko; Aleksandr G. Kostanyants; Gleb A. Neustroev (Вестник Московского Университета. Серия 20: Педагогическое образование)
Background. The article is based on the analysis of the role of education in preserving the national and economic security of the state in modern society. The study is aimed at establishing the scientific and practical possibilities for strengthening the base of the future well-being of the nation and the security of the country on the substantiation basis of interdependence between the national security of the state and the development of education.